Stimulated by laser light exoelectron emission from solid Ar pre-irradiated by an electron beam: Electronic Processes in Cryocrystals - Gumenchuk, G.B.; Ponomaryov, A.N.; Belov, A.G.; Savchenko, E.V.; Bondybey, V.E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
Spatially separated stable charge centers, self-trapped holes and trapped electrons, were generated in Ar cryocrystals by a low-energy electron beam. A combination of the cathodoluminescence (CL) and photon- stimulated exoelectron emission (PSEE) methods was used to monitor center formation and selected relaxation channel – exoelectron emission. It was found that photon-promoted electron current decreased exponentially under irradiation with the laser operating in the visible range. Influence of the laser parameters (power and wavelength) on the characteristic lifetime of exoelectron emission is discussed. Effective bleaching of the low-temperature peaks of thermally stimulated exoelectron emission by the laser light in a visible range was observed.